The future of Swiss hydropower: How to distribute the risk and the profits? - Mirjam Kosch; Regina Annette Betz; Thomas Geissmann; Moritz Schillinger; Hannes Weigt (Swiss Journal of Economics and Statistics, 2021)
Low electricity prices put economic pressure on hydropower companies. A more flexible water fee design can counteract this pressure and support hydropower companies during times when market revenues are low. However, this comes at the cost of lower revenues for resource owners. Using a sample of cost data for 62 companies and revenue data derived from an electricity market model, we have quantified this trade-off for the case of Switzerland. We found that electricity market price developments dominate changes in water fees and that for the profitability of hydropower, electricity prices are more important than water fee levels. However, with electricity prices of around CHF 40 per MWh, water fees can make the difference between profit and loss. Therefore, while flexible water fee regimes shift the market risk from producers to resource owners to some extent, the extent of this risk shift depends on the detailed design of the flexible regime.
Keywords: 330; Hydropower; Water fees; Natural resource rents; Distributional impact